2008
DOI: 10.1111/j.1525-1438.2007.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of the close surveillance policy for stage I female germ cell tumors of the ovary and other sites

Abstract: Ovarian germ cell tumors are rare but very curable at all stages of disease. There is good evidence that surveillance for stage I dysgerminomas is a safe option although many centers worldwide still advocate adjuvant chemotherapy for stage IA nondysgerminomatous tumors, despite the significant risk of developing long-term treatment side effects. Here, we review the safety of our ongoing surveillance program of all stage IA female germ cell tumors. Thirty-seven patients (median age 26, range 14-48 years) with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(69 citation statements)
references
References 31 publications
2
66
1
Order By: Relevance
“…Patterson might help in their preoperative diagnosis. They found that most of the collision tumors had radiologic clues such as the presence of nonfatty fluid in the cyst and a large solid component in the ovarian mass, which pointed toward the presence of two different tumors [20]. Such clues, in addition to frozen section analysis, could help in deciding on further management, particularly the type and extent of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Patterson might help in their preoperative diagnosis. They found that most of the collision tumors had radiologic clues such as the presence of nonfatty fluid in the cyst and a large solid component in the ovarian mass, which pointed toward the presence of two different tumors [20]. Such clues, in addition to frozen section analysis, could help in deciding on further management, particularly the type and extent of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This schedule is based on the experience managing seminomas in males and the reports by Patterson et al [112] and Dark et al [113]. This pragmatic follow-up schedule and has not been tested in randomized trials.…”
Section: Postoperative Management and Follow-up Of Dysgerminomamentioning
confidence: 99%
“…Patients who have Stage I tumors and who are offered surveillance need to be seen regularly and one option is to utilize the follow-up regimen presented above [113]. Patients who have had chemotherapy have a lower risk of recurrence and the frequency of CT scans can be reduced, which is similar to the approach for testicular germ cell tumors [112]. Each follow-up visit should involve taking a medical history, physical examination, and tumor marker determination.…”
Section: Chemotherapy For Dysgerminomamentioning
confidence: 99%
“…For unstaged tumours with good prognosis (dysgerminoma or grade 1 immature teratoma), surveillance alone is an option for those with normal tumour markers and postoperative imaging. However, patients with persistent disease on CT or raised tumour markers should ideally have staging surgery, as they could avoid adjuvant chemotherapy if stage 1A disease is confirmed (23). Avoidance of further surgery but proceeding with adjuvant chemotherapy with careful tumour marker monitoring is an alternative.…”
Section: Surgical Approaches I Primary Surgery a Non-fertility-spamentioning
confidence: 99%